Knowledge, Attitudes, and Practice of HIV/AIDS Members and Nonmembers Kelompok Siswa Peduli AIDS dan Narkoba - Wiriyana, I Gusti Ngurah Agung; Hanim, Diffah; Lestari, Anik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: HIV/AIDS is a contagious disease that attacks the immune system so the body becomes extremely vulnerable to infection of other diseases. Kelompok Siswa Peduli AIDS dan Narkoba (KSPAN) is formed to increase psychomotor aspects and life skills of students in the prevention of HIV/AIDS. This study aimed to determine whether there are differences knowledge and attitudes into practice of HIV/AIDS on members and nonmembers of Kelompok Siswa Peduli AIDS dan Narkoba.Â Â Methods: This study was an observational study with cross sectional analytic. Sampling was done by multi stage random sampling with a sample of 186 high school students in Denpasar. Data were collected through filling questionnaires-related knowledge, attitudes and practice, then analyzed the differences between members and nonmembers KSPAN used chi square (x2). Results: The results showed significant differences in knowledge, attitudes, and practice between members and nonmembers of KSPAN (p<0.001). Conclusions: There were a significant differences in knowledge, attitudes, and practice of HIV/AIDS on members and nonmembers of KSPAN, where knowledge, attitudes, and practice of the members better than nonmembers of KSPAN. Keyword: HIV/AIDS, HIV/AIDS Prevention, Knowledge, Attitude, Practice